2015
DOI: 10.1002/ppsc.201500168
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Enhancement of P3HT‐Based OTFTs upon Blending with Au Nanorods

Abstract: The mobility enhancement of organic thin‐film transistors based on poly(3‐hexylthiophene) (P3HT) by incorporating gold nanorods (Au NRs) is reported. Through varying the doping concentration and surface modifier of the Au NRs in P3HT matrix, the P3HT/Au composite with 0.5 mg mL−1 pyridine‐capped Au NRs exhibits a hole mobility of 0.059 cm2 V−1 s−1, this value is seven times higher than that of pristine P3HT. This remarkable improvement of mobility originates from the enhanced crystallinity and optimized orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The mobilities of P 0.2 and P 0.4 also increased to 1.9 × 10 −3 and 2.7 × 10 −3 cm 2 V −1 s −1 , respectively. This result is consistent with the previous research . Both results obtained from the FETs and SCLC methods proved that a higher charge mobility was induced by the addition of AuNRs, which will play a key role in hole collection and transport, and finally determine its improved photovoltaic performance.…”
Section: Summary Of the Photovoltaic Parameters For The Pscs Doped Wisupporting
confidence: 92%
See 1 more Smart Citation
“…The mobilities of P 0.2 and P 0.4 also increased to 1.9 × 10 −3 and 2.7 × 10 −3 cm 2 V −1 s −1 , respectively. This result is consistent with the previous research . Both results obtained from the FETs and SCLC methods proved that a higher charge mobility was induced by the addition of AuNRs, which will play a key role in hole collection and transport, and finally determine its improved photovoltaic performance.…”
Section: Summary Of the Photovoltaic Parameters For The Pscs Doped Wisupporting
confidence: 92%
“…To achieve the maximum efficiency of the incident light, the incorporation of AuNRs into the HTL rather than the ETL of PSCs with the n–i–p structure would be a better choice. Moreover, previous research has also revealed that AuNRs are beneficial to the orientation and crystallinity of P3HT and increase the hole mobilities . The obtained hole mobilities of P3HT, in combination with AuNRs in an organic thin‐film transistor (OTFT), showed a seven times higher value (0.059 cm 2 V −1 s −1 ) compared with that of pristine P3HT.…”
Section: Summary Of the Photovoltaic Parameters For The Pscs Doped Wimentioning
confidence: 87%
“…Notably, the mobility variation of the 1:20 Au NRs doped device increased significantly to 35%, compared with the pristine device (nearly 8.7%) at 18 ppm NO 2 (figure 3(f)). The migration of charge carriers in polycrystalline films associates with both charge transport in grain and hopping in between adjacent grains under electric fields which could be observed in the variation of mobility [28,31]. We attribute the phenomenon to the improved electronic coupling between TIPS-pentacene molecules and the increased GBs in the OSC film, and this conclusion is further supported by the observation of the TIPS-pentacene film morphologies [20].…”
Section: Resultssupporting
confidence: 61%
“…In the case of PNC comprising a semicrystalline semiconducting polymer, the organization or spatial dispersion of NMs within self-assembled semicrystalline system itself is a topic of great interest to the scientific community for the development of functional hybrid materials, and also for the improvement of its power conversion efficiencies and charge transport properties. Recently, ZnO, TiO 2 , CdSe, and Au NMs have been utilized in the P3HT-based organic solar cells to increase their power conversion efficiencies. Also, attempts are on to understand the effect of different NMs on the charge transport properties of P3HT-based OTFTs. In particular, large number of investigations have already been carried out for the P3HT-AuNM system; ,, even then the effects of AuNMs on the charge transport properties and device performances are not very clear. This is primarily due to the lack of information about the dispersion and locations of the NMs in the film.…”
Section: Introductionmentioning
confidence: 99%